2016
DOI: 10.1039/c6ra18879f
|View full text |Cite
|
Sign up to set email alerts
|

The oleanolic acid derivative, 3-O-succinyl-28-O-benzyl oleanolate, induces apoptosis in B16–F10 melanoma cells via the mitochondrial apoptotic pathway

Abstract: Antiproliferative and proapoptotic effects of 3-O-succinyl-28-O-benzyl oleanolate on B16–F10 skin-melanoma cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…Compared with its natural precursor (OA), OADP is 718 times more effective in HepG2 cells, after 72 h of treatment [ 8 ]. Furthermore, OADP induces morphological changes that are characteristic of apoptosis [ 8 , 23 , 25 , 26 , 27 , 38 ], such as chromatin condensation and fragmentation, as evidenced by fluorescence microscopy. This effect appears to be selective for the tumor cell line, because the cytotoxicity found in the WRL68 non-tumor human embryonic liver cells was 39 times lower than in HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with its natural precursor (OA), OADP is 718 times more effective in HepG2 cells, after 72 h of treatment [ 8 ]. Furthermore, OADP induces morphological changes that are characteristic of apoptosis [ 8 , 23 , 25 , 26 , 27 , 38 ], such as chromatin condensation and fragmentation, as evidenced by fluorescence microscopy. This effect appears to be selective for the tumor cell line, because the cytotoxicity found in the WRL68 non-tumor human embryonic liver cells was 39 times lower than in HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, our groupdescribed the anticancer properties of different triterpenoids, such as maslinic acid (MA) [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ] and the OA derivative, 3- O -succinyl-28- O -benzyl oleanolate [ 27 ]. We also determined the underlying molecular mechanism associated with the anticancer effects of MA in Caco-2 and HT29 colon cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, small organic molecules have been described with anti-cancer and anti-inflammatory properties useful as drugs [44,45]. Currently, has been reported that metal complexes possess remarkable advantages that render them as attractive alternatives to small organic molecules for the development of potential therapeutic agents, among others they show higher half-lives to allow their preferential tissue accumulation, due to their highest vascular permeability that permits their retention on tumor tissues [46].…”
Section: Raw 2647 Cell Viabilitymentioning
confidence: 99%
“…MA, C 30 H 48 O 4 (2α,3β-dihydroxyolean-12-en-28-oic acid) is a natural pentacyclic triterpene, also known as crataegolic acid and derived from its structural analogue, oleanolic acid ( Figure 1 ). It is formed by 30 carbon atoms grouped into five cycles that, as substituents, have two methyl groups each on the C-4 and C-21 carbons; single methyl groups on the C-8, C-10 and C-15 carbons; two hydroxyl groups each on the C-2 and C-3 carbons; one carboxyl group on the C-28 carbon; and a double bond on the C-12 and C-13 [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%